THE INFLUENCE OF WORK ETHIC AND WORKLOAD ON THE PERFORMANCE OF BONDOWOSO EDUCATION OFFICE EMPLOYEES, THROUGH WORK DISCIPLINE AS AN INTERVENING VARIABLE - Churoida Hadyaningrum; Toni Herlambang; Moh Halim (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of work ethic and workload on the performance of employees of the Bondowoso Education Office with work discipline as an intervening variable. This study uses a quantitative approach with a survey method of employees within the Bondowoso Education Office. The results of the study show that work ethic and workload each have a significant effect on employee performance. In addition, work ethic and workload have also been shown to have a positive effect on work discipline, while work discipline directly has an impact on improving employee performance. The path analysis revealed that work discipline mediates the influence of work ethic and workload on employee performance, so work discipline is an important factor that strengthens the relationship between the two variables on performance. These findings affirm the importance of strengthening the value of work ethic, workload management, and improving discipline as the main strategies in efforts to optimize employee performance at the Bondowoso Education Office.